Case Report: Multiple cerebral infarctions in a patient with hereditary hemorrhagic telangiectasia following a fall - Gu, Linting; Chen, Sheng; Li, Wenwei; Ye, Fanlong (Frontiers in Genetics, 2025)
Hereditary hemorrhagic telangiectasia (HHT), also known as Rendu-Osler-Weber syndrome, is an autosomal dominant disorder characterized by arteriovenous malformations (AVMs) affecting multiple organs. This case report presents a rare case of a 62-year-old female with multiple cerebral infarctions following a fall, subsequently diagnosed with HHT. Clinical features included recurrent epistaxis, tongue telangiectasias, and pulmonary AVMs (PAVMs). Genetic testing identified a novel duplication mutation in the ENG gene, c.680_687dupACTCGGCC (p.G230Tfs*8). Brain MRI revealed multiple unusual infarctions, with SWI findings indicating cerebral microvascular abnormalities. These findings highlight the potential role of chronic hypoperfusion and hemodynamic dysregulation, in addition to paradoxical embolism, in HHT-related stroke mechanisms. The patient’s management included antiplatelet therapy adjustment and recommendations for regular imaging and genetic counseling. This case underscores the importance of considering HHT in acute ischemic stroke patients with vascular abnormalities and emphasizes the need for further research into the complex pathophysiology of HHT-related strokes.